Pulmonary Kaposi Sarcoma without Respiratory Symptoms and Skin Lesions in an HIV-Naïve Patient: A Case Report and Literature Review - Cristina Micali; Ylenia Russotto; Alessio Facciolà; Andrea Marino; Benedetto Maurizio Celesia; Eugenia Pistarà; Grazia Caci; Giuseppe Nunnari; Giovanni Francesco Pellicanò; Emmanuele Venanzi Rullo (MDPI AG, 2022)
Kaposi sarcoma (KS) is a multifocal lympho-angioproliferative, mesenchymal low-grade tumor associated with a γ2-herpesvirus, named Kaposi sarcoma-associated virus or human herpesvirus (KSHV/HHV8). The lung is considered a usual anatomical location of KS, despite being infrequent, often in association with extensive mucocutaneous lesions and very uncommonly as an isolated event. We report a case of a pulmonary KS (pKS) in a human immunodeficiency virus (HIV) naïve patient, which was atypical due to a lack of cutaneous involvement and an absence of respiratory symptoms. The pKS was initially identified as a tumoral suspected nodular lesion and only after immunohistochemical analysis was it characterized as KS. Furthermore, the diagnosis of pKS led to the discovery of the HIV-seropositive status of the patient, previously unknown. Our report underlines the importance of considering pKS even without skin lesions and as a first manifestation of HIV infection. We also reviewed literature on the current knowledge about pKS in people living with HIV (PLWH) to underline how one of the most common HIV/acquired immunodeficiency syndrome (AIDS) associated tumors can have a challenging localization and be difficult to recognize.